PENGARUH PENGGUNAAN MODEL EXPLICIT INSTRUCTION TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI RUPA DI SMP N 4 PADANG - Dwi Sri Mariyani, Drs. Yusron Wikarya, M.Pd., Dra. Lisa widiarti, M.Sn. (Universitas Negeri Padang, 2018)
The main purpose of this research was to test whether there was any influence from the use of Explicit Instruction learning model to the students' learning outcomes in Art learning in SMP N 4 Padang. The research method used was quantitative research type quasi experiment. The population in the study is all students of SMP N 4 Padang. While the sample was a class VIII students who are following the material of learning art. In sampling, the technique used was purpose random sampling. While for data analysis technique, this research use hypothesis test by using t test with level of significant 0.05. Based on the results of the research, it can be seen that the results of student learning in SMP N 4 Padang in the experimental class in the learning applying the Explicit Instruction model, it gets higher learning outcomes when compared to the control class in the learning has not applied the Explicit instruction model.Keywords : Model Explicit Instruction, and Student Learning Results